1981
DOI: 10.1017/s002202990002152x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding potassium iodate to milk before UHT treatment: II. Iodate-induced proteolysis during subsequent aseptic storage

Abstract: The addition of potassium iodate to milk at 0-1 mM before UHT treatment resulted in rapid breakdown of a s -and /?-casein during subsequent aseptic storage. Maximum rates of proteolysis were observed at storage temperatures of 37-45 °C, but the reaction was strongly inhibited by storage at 55 °C and by increased holding time at 140 °C during the UHT sterilization. Iodate-induced proteolysis of purified a sland /?-casein was detected only with solutions in the serum phase of raw milk; no proteolysis occurred wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The exact mechanism of thermal denaturation of the serine proteinases PA with β-lactoglobulin remains unknown, but S-S/S-H interactions similar to those already described for the serine proteinase plasmin [31] could be involved. In agreement, considerable PA activity was apparent after heat treatment of a high somatic cell count milk in the presence of the oxidizing agent KIO 3 [23] which is known to inhibit the effect of SH-containing whey proteins like β-lactoglobulin during the heating process [13,43].…”
Section: Influence Of -Lactoglobulin On Thermal Inactivation Of the Isupporting
confidence: 58%
“…The exact mechanism of thermal denaturation of the serine proteinases PA with β-lactoglobulin remains unknown, but S-S/S-H interactions similar to those already described for the serine proteinase plasmin [31] could be involved. In agreement, considerable PA activity was apparent after heat treatment of a high somatic cell count milk in the presence of the oxidizing agent KIO 3 [23] which is known to inhibit the effect of SH-containing whey proteins like β-lactoglobulin during the heating process [13,43].…”
Section: Influence Of -Lactoglobulin On Thermal Inactivation Of the Isupporting
confidence: 58%
“…Addition of 01 niM-KI0 3 to milk before UHT treatment resulted in rapid breakdown of the caseins during storage at 37 °C, whereas the other oxidizing agents studied, H 2 O 2 , KMnO 4 and K 2 Cr 2 0 7 , had no effect even though the redox potentials of these oxidizing agents are higher than that of iodate. Skudder (1981) found that KI0 3 , NaI0 3 and KIO 4 were the only additives which accelerated proteolysis of casein during storage of milk samples subjected to simulated UHT treatment; KBrO 3 , NaClOg and KI had no effect. The special oxidizing power of KI0 3 has been .…”
Section: Resultsmentioning
confidence: 92%
“…A simulated UHT treatment, similar to that described by Skudder (1981), was used. Quantities of milk or casein samples (50 fi\) were placed in melting-point capillary tubes (100 mm long, 0-9-1-0 mm diam.…”
Section: Processing and Storage Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus measurement of plasmin activity has become necessary in milk and dairy products. Different methods have been used in attempts to quantify the enzyme, such as electrophoresis (Driessen & Van der Waals, 1978;Eigel et al 1979;Skudder, 1981;Andrews, 1983), 14 C-radiolabelling and chromatography (Barry & Donnelly, 1981), colorimetric measurements of the breakdown products (de Rham & Andrews, 1982) and use of artificial substrates (Reimerdes et al 1979). Two simple and sensitive methods have recently been described using chromogenic (Rollema et al 1983) or fluorogenic tripeptides (Richardson & Pearce, 1981).…”
mentioning
confidence: 99%